Consensus on a social return on investment model of physical activity and sport: a Delphi study protocol - Nieto, I.; Mayo, X.; Davies, L.; Reece, L.; Strafford, B. W.; Jimenez, A. (Frontiers in Sports and Active Living, 2024)
Background Physical activity and sport (PAS) have been related to many health outcomes and social benefits. The main aim of this research is to build a Social Return on Investment (SROI) model of PAS based on experts' opinion to clarify the domains of impact and how to measure and value them.Methods and Analysis A Delphi method will be employed with a systematic review on the SROI framework applied to PAS and initial interviews with experts informing the design of the Delphi survey statements. Three iterative rounds of communication with the expert panel will be carried out. Participants will indicate their level of agreement with each statement on a five-point Likert scale. During the second and third iterative rounds, experts will reappraise the statements and will be provided with a summary of the group responses from the panel. A statement will have reached consensus if ≥70% of the panel agree/strongly agree or disagree/strongly disagree after round 3. Finally, group meetings (3-4 experts) will be conducted to ask about the measurement and valuation methods for each domain.Discussion The final goal of this project will result in the design of a toolkit for organizations, professionals, and policymakers on how to measure the social benefits of PAS.